2005
DOI: 10.1111/j.0105-2896.2005.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between immunodominance, DM editing, and the kinetic stability of MHC class II:peptide complexes

Abstract: Immunodominance refers to the restricted antigen specificity of T cells detected in the immune response after immunization with complex antigens. Despite the presence of many potential peptide epitopes within these immunogens, the elicited T-cell response apparently focuses on a very limited number of peptides. Over the last two decades, a number of distinct explanations have been put forth to explain this very restricted specificity of T cells, many of which suggest that endosomal antigen processing restricts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(136 citation statements)
references
References 165 publications
4
129
3
Order By: Relevance
“…These observations suggest that, in general, a binding affinity that is neither too high nor too low may be optimal for epitope recognition during infection. It has also been suggested that peptide stability correlates best with immunodominance (54,55,61). However, in our hands, peptide stability did not correlate significantly better with immunodominance than did equilibrium binding measurements.…”
Section: Discussioncontrasting
confidence: 78%
“…These observations suggest that, in general, a binding affinity that is neither too high nor too low may be optimal for epitope recognition during infection. It has also been suggested that peptide stability correlates best with immunodominance (54,55,61). However, in our hands, peptide stability did not correlate significantly better with immunodominance than did equilibrium binding measurements.…”
Section: Discussioncontrasting
confidence: 78%
“…In this setting, Ag abundance has been hypothesized to influence the magnitude of CD4 responses (68). In our data set, proteins that are present in purified virion preparations were recognized significantly more often than proteins that are not detected in virions.…”
Section: Discussionmentioning
confidence: 78%
“…CD4 immunodominance is noted in the MHC class II-restricted response to LACK in Leishmania-infected H-2 d mice (67). Several factors influence CD4 immunodominance, including HLA-DM, the susceptibility of epitope-flanking regions to proteolysis, trafficking of proteins to various membranous compartments, especially in the setting of intracellular Ag synthesis, and innate activation of APC (68). MHC allelic variation of course plays a role, but probably less so than for CD8 responses due to the greater promiscuity for peptide binding of MHC class II compared with MHC class I.…”
Section: Discussionmentioning
confidence: 99%
“…The cofactor tapasin additionally edits the peptide repertoire that is loaded onto class I molecules in favor of those with slow dissociation kinetics [10]. This is a similar function to that described for DM in MHC class II loading [11].…”
Section: Introductionmentioning
confidence: 89%